Clinical and Genetic Spectrum of Encephalopathy in the Korean Pediatric Population - Woo Joong Kim; Young Kyu Shim; Young Jun Ko; Soo Yeon Kim; Hunmin Kim; Byung Chan Lim; Hee Hwang; Jieun Choi; Ki Joong Kim; Jong-Hee Chae (Korean Child Neurology Society, 2021)
Purpose Syntaxin-binding protein 1 (STXBP1) mutations are known to result in various phenotypes including Ohtahara syndrome, West syndrome, and autism, collectively referred as STXBP1 encephalopathy. This study aimed to expand our understanding of the genotype-phenotype spectrum of STXBP1 encephalopathy in the Korean pediatric population. Methods Ten patients with STXBP1 mutations were enrolled for a retrospective chart review. The patients were investigated for developmental delay of unknown cause and epileptic encephalopathy at a single center. Results Ten different STXBP1 mutations were identified. Three mutations had not previously been reported (c.1212A>C, c.1497C>G, c1030-2A>G). Eight patients showed early-onset epileptic encephalopathy as the main feature, while the main feature was developmental delay and non-epileptic movements in two patients. The most commonly seen electroencephalographic change was focal/multifocal epileptiform discharges, which were observed in nine patients (90%). The classical burst-suppression pattern was observed in four patients, two of which evolved to show hypsarrthymia. All patients with seizures had drug-resistant epilepsy. The patients suffered from severe developmental delay regardless of seizure frequency. Six patients showed an associated movement disorder or behavioral disorder. Conclusion This study describes the STXBP1 encephalopathy patients in Korean pediatric population, further expanding knowledge of its phenotype spectrum.